Technical System Strategy Review to Improve the Medical Examination of Elbow Dislocations - Forster, Fabian; Meindl, Markus; Gehring, Jonas; Mangold, Lucas; Simon, Michael; März, Martin (2026)
The elbow dislocation is the second most common human dislocation. In case of an injury, a fast and correct diagnosis is essential for a good convalescence. The diagnosis depends on the attending doctor's experience and is sometimes subjective. A technical device should assist the doctor during the first and follow-up examination to eliminate this subjectivity. This generates verifiable diagnostics within the usage of tomographic equipment. To reach this goal, this paper describes the first steps of developing this still-unknown system. Therefore, the knowledge of elbow examination was elaborated and transferred to technical requirements. Later, functional groups were built, and technical solutions were compiled. The best-rated solution yields the theoretical functional principle. To verify the principle and to gather further knowledge, prototypes are designed. The physical realization is made with Fused Deposition Modeling. Different actor principles are evaluated. Tests in computer tomography verified the possible use case. A functional test with a skeleton arm model in the technical solution proves its suitability. The requirements are confirmed and missing data are obtained. The application is registered for patent. Improvements are determined and a technical more sophisticated prototype is in progress. Cadaver arm tests are planned to validate the aspects medicall
https://cris.fau.de/converis/publicweb/Publication/354503096
Keywords: elbow; injury; medicine; computer tomography; mechatronics